2017
DOI: 10.1002/qua.25514
|View full text |Cite
|
Sign up to set email alerts
|

Density‐functional theory study of the interaction mechanism and optical properties of flavonols on the boron nitride nanotubes

Abstract: The flavonols are natural pigments with multiple colors. They are found ubiquitously in plants and are relevant to flower colors and the UV protection in plants. Their antioxidant, anticancer, and anti‐allergic features attract researchers much attention to explore their potential applications in biological and nanomedical areas. In this study, the interaction mechanism and optical properties of four representative flavonols, on both the surface and confined in the single‐walled boron nitride nanotubes (BNNTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…The TD-DFTB method has been applied to predict the optical properties and excited-state electron dynamics of large systems, such as semiconductor nanoparticles, 8688 silicon quantum dots, 8992 and other nanoscale systems. 9395 More recently, Sanchez and co-workers have investigated the relaxation dynamics of LSPR and the effect of oxidation on the plasmonic properties of metal nanoclusters. 9698 Their results have shown that the TD-DFTB method can produce the expected size effect for the LSPR of such systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TD-DFTB method has been applied to predict the optical properties and excited-state electron dynamics of large systems, such as semiconductor nanoparticles, 8688 silicon quantum dots, 8992 and other nanoscale systems. 9395 More recently, Sanchez and co-workers have investigated the relaxation dynamics of LSPR and the effect of oxidation on the plasmonic properties of metal nanoclusters. 9698 Their results have shown that the TD-DFTB method can produce the expected size effect for the LSPR of such systems.…”
Section: Introductionmentioning
confidence: 99%
“…One possible candidate that can account for quantum mechanical effects in large systems is the density functional tight binding (DFTB) method , and its time-dependent formalism (TD-DFTB), , which aims to achieve the accuracy of DFT methods and the efficiency of tight-binding-based methods. The TD-DFTB method has been applied to predict the optical properties and excited-state electron dynamics of large systems, such as semiconductor nanoparticles, silicon quantum dots, and other nanoscale systems. More recently, Sanchez and co-workers have investigated the relaxation dynamics of LSPR and the effect of oxidation on the plasmonic properties of metal nanoclusters. Their results have shown that the TD-DFTB method can produce the expected size effect for the LSPR of such systems . In another recent work, Ilawe et al utilized the real-time TD-DFTB formalism to understand the electron dynamics of plasmonic antennas.…”
Section: Introductionmentioning
confidence: 99%
“…DFTB was also developed in order to study adsorption of organic molecules on carbon surfaces, for example transition metal complexes (porphyrin and porphycene) on graphene [313] or small molecules (H 2 O, CH 4 , NH 3 ) on defective carbon nanotubes which were all found to physisorb on the nanotubes, except NH 3 which also chemisorbs [314]. Optical properties of natural pigments (flavonols) adsorbed on boron nitride nanotubes were also analyzed using DFTB (Figure 8) [315]. Some DFTB surface adsorption studies have also given rise to reactivity studies, for example water splitting on anatase (001) [316] or H 2 dissociation on plutonium [317].…”
Section: Supported or Embedded Systemsmentioning
confidence: 99%
“…In addition, they are stable in air and in an inert atmosphere. Based on these fantastic properties, BNNTs have different applications such as in biomedical applications specially in drug delivery and bone scaffolding, electronic and microelectronic mechanical devices, and energy storage [3,5,6]. Also, they can be used as alternative to CNTs to help enhance strength of materials [4].…”
Section: Introductionmentioning
confidence: 99%